KLASIFIKASI PEMEROLEHAN NOMINA (KAJIAN PSIKOLINGUISTIK PADA ANAK USIA 3-5 TAHUN) - Suryati Suryati; Fitri Nurlaela; Wikanengsih Wikanengsih (IKIP Siliwangi, 2018)
This research is motivated by the researcher's curiosity about the acquisition of noun words in children aged 3-5 years. Aims to know the classification of the basic noun words, derived nouns, and reduplications. This research started with observation activity to Respondent 1 3 year old, Respondent 2 4 years old, and Respondent 3 aged 5 years. After observing the 3 respondents, the researcher collects the data and processes the data using qualitative descriptive method, that is the method that describes the fact or fact according to the data obtained. This research is descriptive, meaning that the vocabulary that shows noun will become the main data of research. The results of the study show the class classification of basic Nomina, derived Nomina and Reduplication. Respondents 1 who were 3 years old received 50 words of base noun, 8 said nouns, 3 words reduplication. Respondents 2 4 years old received 43 words of base noun, nine derived nouns, 7 words reduplication, and Responde 3 aged 5 years obtained 73 words nouns, 7 words nouns derived, 6 word reduplication.